2019
DOI: 10.1021/acsami.9b05564
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Interlayer Spacing in Cobalt–Manganese Layered Double Hydroxide Guiding Transformation to Layered Structure for High Supercapacitance

Abstract: Cobalt–manganese layered double hydroxide (CoMn-LDH) has been known as a highly desired cathode material used with an alkaline electrolyte. However, the layered double hydroxide structure is unstable and changes almost instantly in alkaline solution due to the instability of a manganese­(III) ion. Thus, it is important to investigate the true active phase for designing efficient electrode materials. In this work, the metal–organic framework is used as a templating precursor to derive CoMn-LDH from three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 46 publications
4
65
0
Order By: Relevance
“…This architecture can effectively prevent the restacking of rGO and the aggregation of NiCo 2 O 4 and has fast reversible redox reactions and long-term stability for supercapacitors. Liu et al [70] synthesized ultrathin NiCoAl-LDH (m-LDH) nanosheets and N-doped reduced graphene oxide (NRG) nanohybrids by alkaline etching of pre-synthesized ultrathin NiCoAl-LDH nanosheets and electrostatic assembly. The chemical states of the active Ni/Co elements were modulated by the alkaline etching, and more oxygen vacancies were created in the m-LDH nanosheets.…”
Section: Chemical Exfoliation Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…This architecture can effectively prevent the restacking of rGO and the aggregation of NiCo 2 O 4 and has fast reversible redox reactions and long-term stability for supercapacitors. Liu et al [70] synthesized ultrathin NiCoAl-LDH (m-LDH) nanosheets and N-doped reduced graphene oxide (NRG) nanohybrids by alkaline etching of pre-synthesized ultrathin NiCoAl-LDH nanosheets and electrostatic assembly. The chemical states of the active Ni/Co elements were modulated by the alkaline etching, and more oxygen vacancies were created in the m-LDH nanosheets.…”
Section: Chemical Exfoliation Recombinationmentioning
confidence: 99%
“…Some other anions such as OH − , NO 3 − , SO 4 2− , and Cl − are promising candidate anions and have been widely researched. Wang et al [ 61 ] reported the effect of NO 3 − , SO 4 2− , and Cl − anions on the structure and capacitive performance of MnCo‐LDHs, as shown in Figure a. In detail, the different interlayer anions dramatically affect the phase transformation, structure, and charge storage properties of the MnCo‐LDH materials.…”
Section: Chemical Modification Of Ldhsmentioning
confidence: 99%
“…Second, the interlayer anions can tailor the microporous structure and provide more active sites, leading to an enhanced capacitive performance. [9,18] Positive chargesi nt he host layers and weak interactions of interlayer anions with the host-layer cations enablet he LDH to adsorb various types of anionic species in the interlayer spacing by directi ntercalation or by anion exchange. Several molecules (such as dodecyl sulfate ions, [52] glucose, [22] ethylene glycol, [19] and acetate [53] )h ave been intercalated into the interlayers of LDHs to constructS Ce lectrode materials.…”
Section: Tuning Of Anions and Interlayer Spacingmentioning
confidence: 99%
“…[52] Our group investigated the effect of NO 3 À ,C l À ,a nd SO 4 2À anions on the structure and capacitive performances of CoMn LDH. [18] The intercalationa nionss trongly affect the layer structure, phase transformationp rocess, and charge-storage properties of the CoMn LDH electrode materials. In particular,S O 4 2Àintercalated CoMn LDH shows the largesti nterlayer spacing of 1.08 nm, and the most stable layered structure in KOH electrolyte compared with those of NO 3 À -a nd Cl À -intercalated CoMn LDHs.…”
Section: Tuning Of Anions and Interlayer Spacingmentioning
confidence: 99%
See 1 more Smart Citation